Overcoming limitations for antibody-based therapies targeting γδ T (Vg9Vd2) cells - Paniagua-Herranz, Lucía; Díaz-Tejeiro, Cristina; Sanvicente, Adrián; Bartolomé, Jorge; Nieto-Jiménez, Cristina; Ocana, Alberto (Frontiers in Immunology, 2024)
Therapeutic strategies targeting non-adaptive immune cells are currently in clinical development. γδT cells are a small subtype of T cells (1-10% of total T cells) that mediate their effector function without the necessity of the antigen presenting machinery, and also share functional properties with innate cells. Among the different γδT subtypes, antibodies against Vγ9Vδ2T have reported signs of clinical efficacy in early clinical studies. In this review we describe the biology of this subtype of non-conventional T cells and provide insights into the mechanism of action of novel antibodies that activate these cells. We will focus on antibodies targeting the BTN3A ligand and bi-specific γδT cell engagers. We will review in detail the advantages of these strategies including the potential for overcoming mechanisms of resistance to check point inhibitors, or the much more adequate safety profile compared with agents activating classical T cells. Limitations identified during the first studies in humans and strategies to overcome them will be revised and discussed. Finally, clinical options for future clinical development will be suggested.